Hegel's critique of Kant - Sedgwick, Sally S., 1956- (Oxford : Oxford University Press, 2012)
Sally Sedgwick presents an account of Hegel's critique of Kant's theoretical philosophy. She argues that Hegel offers a critique of and alternative to the conception of cognition that Kant defended in his 'critical' period, and explores Hegel's claim to derive from Kantian doctrines clues to a superior form of idealism.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Kant, Immanuel, -- 1724-1804.